PENGARUH PENGGUNAAN SMARTPHONE TERHADAP KREATIVITAS MAHASISWA BIMBINGAN DAN KONSELING FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS KRISTEN SATYA WACANA - Ester Febryanditha Tahapary (Universitas Kristen Satya Wacana, 2023)
The purpose of this study was to determine the effect of smartphone use on the creativity of the class of 2019. This study used a causal-comparative type of research. The population in this study were students of guidance and counseling class of 2019 SWCU. In this study, the authors used a sampling technique using total sampling. The sample in this study was the student guidance and counseling class of 2019 SWCU. In the data collection technique, each instrument uses a Likert scale. The analytical technique used in this study is simple linear regression analysis using the help of IBM Statistics SPSS 21.0. The results showed that the results of the simple linear regression test that had been carried out were known to be greater than ttable (14,806 > 2.002) with a sig. 0.000 value less than 0.050 (0.000 < 0.050). This means that there is a significant positive effect of smartphone use on creativity. So the hypothesis which states "there is a significant influence on the use of smartphones on the creativity of Guidance and Counseling students for the class of 2019". The variable of smartphone use contributes to creativity by 79.7%, and the rest (20.3%) is influenced by other variables not examined in this study. Keywords: Smartphone use, Creativity